Asiatic cotton can generate similar economic benefits to Bt cotton under rainfed conditions - Romeu-Dalmau, C; Bonsall, M; Willis, K; Dolan, L (Nature Publishing Group, 2015)
American cotton (Gossypium hirsutum L.), transformed with Bacillus thuringiensis Cry genes (Bt G. hirsutum) that confer resistance to lepidopteran pests, is extensively cultivated worldwide. In India, transgenic Bt G. hirsutum was commercially released in 2002 and by 2014 95% of farmers had adopted Bt G. hirsutum. The economic benefits of Bt G. hirsutum over non-Bt G. hirsutum are well documented and include increase in yields, increase in farmers' net revenue and reduction in pesticide application against lepidopteran pests. However, it is unclear to what extent irrigation influences the performance of Bt G. hirsutum on smallholder farming in India, and if, in the absence of irrigation, growing Bt G. hirsutum provides greater economic benefits for Indian smallholder farmers compared with growing the Asiatic cotton Gossypium arboreum L. Here, we compare the economic impact of growing Bt G. hirsutum with growing G. arboreum under rainfed conditions in the Indian state of Maharashtra, and show that G. arboreum can generate similar net revenue, and thus similar economic benefits for smallholder farmers compared with growing Bt G. hirsutum. We also compare the economic impact of growing Bt G. hirsutum under rainfed conditions with growing Bt G. hirsutum under irrigated conditions and show that even though Bt G. hirsutum yields increase with irrigation, the net revenue does not significantly increase because farmers using irrigation spend significantly more than farmers growing Bt G. hirsutum without irrigation. We conclude that our data provide a broader insight into how socio-economic data needs to be incorporated into agro-ecological data when planning strategies to improve cotton farming in India.